Uterine preservation in pelvic organ prolapse and urinary stress incontinence using robot-assisted laparoscopic surgery. Case report. (2020) - Cucinella, Gaspare; Culmone, Silvia; Guastella, Ettore; Gentile, Francesco; De Maria, Francesca; Granà, Roberto; Carlisi, Bruno; Rotolo, Stefano; Calagna, Gloria
Highlights: Pelvic organ prolapse (POP) represents a common and bothersome condition in parous women. The demand to "save" the uterus has fuelled a renewal of the surgical technique. Robotic surgery was conceived with the intent to overcome the limitations of laparoscopic surgery. The characteristics of the robotic system help surgeons to perform conservative management of POP. Abstract: Introduction: To report a case of uterine preservation in pelvic organ prolapse robot-assisted laparoscopic surgery. Presentation of case: The patient is a 42-year old Caucasian woman with pelvic organ prolapse. She previously had undergone a pelvic floor reconstruction with vaginal surgical approach, she had suffered from anorexia nervosa and she had two childbirths with vaginal deliveries. The woman was treated with robotic-assisted laparoscopic sacrohysteropexy and retropubic colposuspension. Discussion: Data suggest that abdominal surgery, typically with an abdominal sacralcolpopexy, provides better objective anatomic outcomes, than vaginal procedures, despite the longer operating times and grater delay in the resumption of activities which can be mitigated by the use of laparoscopic or robotic surgery. Several studies about vaginal approaches suggest that uterus-preserving surgery with vaginal procedures have similar success rates, less blood loss and shorter surgical time compared with hysterectomy. A multicenter study compared laparoscopic sacrohysteropexy with vaginal mesh hysteropexy reported similar one-year cure rates, improvement in pelvic floor symptoms, improvement in sexual function, and satisfaction rates. Conclusion: We found robotic-assisted laparoscopic sacrohysteropexy to be a feasible and successful procedure. Combining robotic retropubic colposuspension to sacrohysteropexy is a safe and efficient approach for the treatment of stress urinary incontinence. Further studies are needed to define the standard surgical steps and confirm the efficacy and the advantages of this procedure.